Estudio de las acciones técnico-tácticas realizadas por los porteros de balonmano ante los lanzamientos de pivote - Carbonell Garcia, V.; Fontaina, S.; Gonzalez, A. (Revista Ciencia del Deporte, 2018)
The aim of this work was to analyze the characteristics of the actions carried out by the elite handball goalkeepers against the pivot throws. The study was based on a qualitative research model, using as an instrument of data collection the interview. Seven international goalkeepers were interviewed. As a results, the importance of the position of the goalkeeper in the area before a throw of the pivot is emphasized, as well as the use of the displacements to diminish the angles of shoot. On the other hand, it was verified the influence of the body size in relation to the decision-making of the goalkeeper. The indicators used by the goalkeepers at the time of decision making are: the placement of the trunk and shoulders; Arm movement; opposition; player trajectory; height and zone where it receives; laterality; orientation of the feet and the turn. Finally, they emphasize the importance of the study of the rival to establish strategies of action.